Single‐Use Technology in the Biopharmaceutical Industry and Sustainability: A Contradiction?. Issue 12 (6th October 2022) - Ottinger, Melanie; Wenk, Irina; Carvalho Pereira, Joana; John, Gernot; Junne, Stefan
Abstract: Single‐use technology has become important in biopharma processes since many years. Despite all the benefits, the generally rising concerns about single‐use material are hitting industrial bioproduction. The subgroup "Sustainability" of the DECHEMA workgroup "Single‐Use Technologies" aims to investigate any potential to quantify sustainability and identify points of concern or contradiction when applying single‐use material. This essay summarizes some facts about its utilization, past and current efforts to define, measure and increase sustainability and recommendations for potential actions. Abstract : Single‐use technology has raised concerns about their contribution to a sustainable bioproduction. This essay summarizes life cycle analyses and provides perspectives to gain an understanding of benefits and drawbacks of the application of single‐use material in up‐ and downstream processing in pharmaceutical production.